Factors Influencing Aggression Among Adolescents in Indonesia: A Literature Review: Faktor-Faktor yang Memengaruhi Remaja di Indonesia Melakukan Agresivitas: Literature Review - Wangsa, Pande Ryan Praba; Tobing, David Hizkia (Utan Kayu Publishing, 2024)
Adolescent aggression has long been a major concern in the fields of educational psychology and sociology, especially in Indonesia where social and cultural dynamics play a role in shaping adolescent behavior. This study is a systematic literature review, examining 30 publications from the years 2014 to 2023 to understand the factors influencing aggression among Indonesian adolescents. This method involved collecting data from various sources accessed through Google Scholar using relevant keywords associated with adolescent aggression. The purpose of this review is to specifically ascertain the effects of internal factors such as emotional maturity, emotional intelligence, and self-control, as well as external factors including peer conformity, parental communication styles, parenting styles, and the intensity of online gaming on aggressive behavior in adolescents. The findings from this analysis are expected to provide deeper insights into effective ways to intervene and prevent aggressive behaviors among adolescents in Indonesia, thereby making a significant contribution to parenting practices, education, and social and mental health policy for adolescents.